Źródła finansowania komunalnych inwestycji infrastrukturalnych – przykład gminy Szadek - Bartosiewicz, Bartosz (Biuletyn Szadkowski, 2008)
Infrastructure development by local governments in Poland is among the most important and the most difficult (in financial terms) local undertakings. In many cases the only possibility to expand or modernise the existing infrastructure is to secure external funding, i.e. to obtain non-budgetary funds. This is particularly important for small communes, where revenues do not meet their needs. Szadek is an example of such a commune. External funding covered about 50% of municipal infrastructure development costs in the period 1995–2007, which is an average value for small communes in the region of Łódź. The commune of Szadek is also an example of insufficient efforts to obtain EU funding for infrastructure development projects intended to enhance the quality of the natural environment and the quality of life of the inhabitants.